As dusk falls: collective decisions about the return to sleeping sites in meerkats. (October 2017) - Gall, Gabriella E.C.; Strandburg-Peshkin, Ariana; Clutton-Brock, Tim; Manser, Marta B.
Abstract : Social animal groups often make consensus decisions about when to return to a sleeping site after a day of foraging. These decisions can depend on extrinsic as well as intrinsic factors, and can range from unshared to shared. Here we investigated how decisions of meerkats, Suricata suricatta, to return to their burrows are coordinated, whether they are shared or monopolized by dominant individuals, and what factors influence the timing and speed of return. Individual meerkats can initiate group movements using 'lead' calls, and groups can change foraging patches using 'move' calls in a quorum response. We found that both call types could be produced during the return to the burrow, with the probability of move calls increasing as sunset approached, and the probability of lead calls increasing with greater distance to the burrow when sunset was imminent. Dominant and subordinate individuals did not differ significantly in move and lead call rate. Further, the time of return was better predicted by the foraging success of all subordinates in the group (with the group returning later when success was low) than by the foraging success of the dominant individuals. This suggests that decisions to return are shared rather than controlled by dominants. The speed of return depended both on extrinsic factors, such as the presence of pups, the time until sunset and the distance to the burrow, and on intrinsic factors such as satiation. Our results indicate that both the speed and timing of the return depend on urgency, and the higher incidence of lead calls when groups are far away from the burrow near dark suggests a possible change in the decision process from shared to unshared as urgency increases. Our study highlights the impact of time constraints during decision-making processes and in particular on the level of decision sharing. Highlights: Activity termination is not well integrated in collective behaviour research. We studied group decisions to end foraging and return to the burrow in meerkats. Dominants did not give 'lead' or 'move' calls more than subordinates. Subordinates' mean weight gain better predicted return time than either dominants'. This suggests that decisions to return are shared rather than driven by dominants.